The Vegetation of the issue in Urbanized Environment (Revista Brasileira Multidisciplinar, 2010)
Population growth and urban expansion have provoked the cultural rootlessness of rural migrants, poverty increase, ecological problems caused by the impermeability of the soil and by atmosphere, water and sound pollution, besides the reduction of the vegetable covering. The rapid expansion of the Metropolitan Region of São Paulo and Campinas has generated socio-environmental impacts, which have been worsened by an inappropriate vision of the environmental issues by the urban managers. The aim of this work has been to analyze the urbanization taking into account the environmental and social aspects of the economic growth , making it possible to suggest actions to avoid the cultural rupture of the population, by means of an urban planning directed to the soil occupation and to the rational use of the soil, as well as the worry with tree planting in the streets and the creation of green areas as a tool for environmental education to contribute to the practicing of citizenship for the transformation of our society in a sustainable one.
Keywords: Urbanization; Economical development; Tree planting; Sustainability